Observation of Pyramidal Lobe and Levator Glandulae Thyroideae and Their Macroscopic Feature and Relation with Whole Thyroid Gland: A Postmortem Study. - Banna, Fakhrul Amin Mohammad Hasanul; Sultana, Zakia; Khalil, Mansur; Begum, Jahan Ara; Begum, Manowara; Islam, Mohammod Towhidul (Medicine Today, 2012)
Back Ground: The thyroid is a brownish red, highly vascular earliest endocrine glandular structure appears in mammal. The size of thyroid gland varies considerably with age, sex, physiologic state, race and geographical location. It is larger and heavier in mature females than in males, and it hypertrophies during menstruation and pregnancy. Diseases of thyroid may need surgical intervention. During thyroid surgery, there is every possibility of occurrence of haemorrhage and recurrent laryngeal nerve injury. So this study is to carry out the macroscopic and microscopic architecture of thyroid gland of different age and sex groups in Bangladeshi people to establish a normal standard. This study will also help in minimizing complications of thyroid surgery and tracheostomy. Study design: Mainly descriptive cross-sectional study with an analytic component. Place and period of study: Department of Anatomy, Sylhet M. A. G. Osmani Medical College, Sylhet, from 1st July 2006 to 30th June 2007. Materials: The study was carried out on 54 autopsied human thyroid glands aged 5 to 65 years. Thyroid glands were collected from unclaimed dead bodies autopsied in morgue of Sylhet M. A. G. Osmani Medical College, Sylhet. Methods: The collected specimens were divided into age group A (10 years and below), group B (11 to 20 years), group C (21 to 30 years), group D (31 to 40 years), group E (41 to 50 years) and group F (51years and above). All specimens were examined morphologically by fine dissection method. Result: Pyramidal lobe and levator glandulae thyroideae were present in 37.04% and 59.26% cases respectively and were situated to the left side of midline in most of the cases. In most of the cases levator glandulae thyroideae had association with apex of pyramidal lobe to the body of the hyoid bone. Conclusion: From observation and results it reached conclusion that the present study will help to increase the information pool on the anatomy of thyroid gland of Bangladeshi people. To establish a normal standard for Bangladeshi people, further studies with large samples from different zones including goitre endemic zones of the country are suggested. Medicine Today 2010 Volume 22 Number 02 Page 83-87 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12440